A mathematical model to set speed limits for vehicles on the highway - Oke, Sunday A.; Bamigbaiye, Ayokunle; Oyedokun, Oluwafemi I.; Charles-Owaba, Oliver E. (Transport, 2006)
The purpose of this paper is to develop a mathematical model that could guide certain speed limits for vehicles on roads. Excessive speeds on roads have been a major indirect cause of deaths on highways due to the sudden impact of vehicles that lead to accidents. The model presented here is developed on a measure of impact force of two vehicles engaged in a head‐on collision. A hypothetical case study was investigated based on the impact of force on the human body. The results showed a variation of speed with occupation position distance. The paper also examines the role of seatbelt as a safety feature for vehicle occupants. Practically, developing a quantitative approach for evaluating the impacts of speed would help road regulatory authorities in reducing accidents and deaths on roads. It would also assist them in tracking “road traffic offenders” by setting controls to which road users must conform.First Published Online: 27 Oct 2010